2021
DOI: 10.1177/2156759x20985835
|View full text |Cite
|
Sign up to set email alerts
|

Play Therapy Courses in School Counselor Training: A Content Analysis of Syllabi From CACREP-Accredited School Counseling Programs

Abstract: The purpose of this study was to conduct a content analysis of the syllabi of play therapy courses offered by school counseling programs that hold accreditation from the Council for Accreditation of Counseling and Related Educational Programs. We collected and analyzed 27 course syllabi to (a) identify trends in the content of these courses and (b) examine whether course objectives are consistent with the American School Counselor Association School Counselor Professional Standards & Competencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Further, university coursework in combination with the institute/professional conference and workshop training in play therapy predicted increased levels in attitudes, knowledge, and skills. The recommendation from these correlations is for more university counseling programs to offer play therapy coursework to give counselors a stronger foundation for counseling children, especially because the research indicated that there is a positive impact on counseling students who take play therapy courses at universities (Shin & Na, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, university coursework in combination with the institute/professional conference and workshop training in play therapy predicted increased levels in attitudes, knowledge, and skills. The recommendation from these correlations is for more university counseling programs to offer play therapy coursework to give counselors a stronger foundation for counseling children, especially because the research indicated that there is a positive impact on counseling students who take play therapy courses at universities (Shin & Na, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The university is where most beginning counselors get a view of what they are supposed to do in sessions. Those who take play therapy courses in university counseling programs are better able to incorporate play therapy skills when working with young children in practice (Shin & Na, 2021). According to the Association for Play Therapy (APT, 2020a), a professional membership organization that provides access to play therapy resources and information (APT, 2020c(APT, , 2020d, only 152 U.S. universities offer play therapy courses.…”
mentioning
confidence: 99%